Borophene: New Sensation in Flatland. Issue 34 (14th July 2020) - Ranjan, Pranay; Lee, Jang Mee; Kumar, Prashant; Vinu, Ajayan
Abstract: Borophene, a 2D allotrope of boron and the lightest elemental Dirac material, is the latest very promising 2D material owing to its unique structural and electronic characteristics of the X3 and β12 phases. The high atomic density on ridgelines of the β12 phase of borophene provides a substantial orbital overlap, which leads to an excellent electron density in the conduction level and thus to a highly metallic behavior. These unique structural characteristics and electronic properties of borophene attract significant scientific interest. Herein, approaches for crystal growth/synthesis of these unique nanostructures and their potential technological applications are discussed. Various substrate‐supported ultrahigh‐vacuum growth techniques for borophene, such as molecular beam epitaxy, atomic layer deposition, and chemical vapor deposition, along with their challenges, are also summarized. The sonochemical exfoliation and modified Hummer's technique for the synthesis of free‐standing borophene are also discussed. Solution‐phase exfoliation seems to address the scalability issues and expands the applications of these unique materials to various fields, including renewable energy devices and ultrafast sensors. Furthermore, the electronic, optical, thermal, and elastic properties of borophene are thoroughly discussed and are compared with those of graphene and its "cousins." Numerous frontline applications are envisaged and an outlook is presented. Abstract : Borophene is considered as one of the most promising 2D nanomaterials, owing to its unique structural and electronic properties. The various synthetic approaches for the fabrication of borophene nanostructures with different phases and morphologies, including free‐standing borophene sheets, are described. The frontline applications of these nanostructures in flexible electronics, sensing, disease diagnosis, catalysis, and hybrid energy storage are also considered.